Corneal Biofilm Plaques: A Novel Clinical Presentation. Issue 6 (June 2019) - Córdoba, Andrea; Graue-Hernandez, Enrique O.; Bermudez-Magner, Jose A.; Ramirez-Miranda, Arturo; Irusteta, Leire; Bautista-de Lucio, Victor M.; Ponce-Angulo, Diana G.; Bautista-Hernandez, Luis A.; Navas, Alejandro
Abstract : Purpose: To report a novel clinical presentation of corneal biofilms, consisting of formation of superficial and recurrent corneal plaques. Methods: Interventional case report. A 9-year-old boy presented with subepithelial, whitish, avascular, and recurrent corneal plaques without any clinical manifestations of active corneal inflammation and/or infection. He had a history of minor ocular trauma; otherwise, his medical history was unremarkable. Results: An excisional biopsy was performed under topical anesthesia. Histological analysis identified these plaques as clusters of gram-negative bacilli surrounded by an extracellular matrix. Samples were further evaluated with special stains (calcofluor white, Flamingo fluorescent dye, propidium iodide, and Gomori–Grocott) that demonstrated biofilm structures. Conclusions: Corneal plaques are a very rare clinical presentation of corneal biofilms that allow prolonged survival of microorganisms even in the absence of prosthetic material and clinical signs or symptoms of corneal active inflammation and/or infection.